2014
DOI: 10.12944/cwe.9.3.02
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Soil Chemical and Physical Properties on Cd Mobility Studied by Soil Thin-Layer Chromatography

Abstract: Heavy metals contamination threat to the environment is a big concern. Predicting the movement of heavy metals such as Cd in soil is an important goal. In this study the effect of soil chemical and physical properties on Cd mobility were done using a thin layer chromatography (Soil TLC). The soils used in this research have a wide range of organic matter (2.1-29 g/kg), pH value (4.9-8.8), CEC (4.1-99 cmol/kg), bases saturation, iron and aluminum oxides to examines its effect on Cd mobility. The (Rf) values obt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2017
2017
2018
2018

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 19 publications
0
3
0
Order By: Relevance
“…Upon studying soil texture in relation to extractable concentrations of Pb and Cu, Qian and others found that metals were generally enriched in the clay fraction; whereas relatively large amounts of available Cu and Pb were noted in the fine sand fraction, they also noted that available Pb concentrations were also high in the clay fraction [53]. Al-Oud and others found that Cd mobility decreases with increasing amounts of iron oxide fractions; silt content and exchangeable Mg 2+ in the soils; and showed that Cd mobility is higher in those soils with a high percentage of sand [54]. Additionally, Bloomfield has found that microbial action has also been observed to mobilize Pb, Zn and Cu from the carbonate and oxide residuals within soils [55] and Ernst established that solubility of metals was also enhanced by the acidification of the soil by bacteria [56].…”
Section: Ellis Island Soil Particle Sizementioning
confidence: 95%
See 2 more Smart Citations
“…Upon studying soil texture in relation to extractable concentrations of Pb and Cu, Qian and others found that metals were generally enriched in the clay fraction; whereas relatively large amounts of available Cu and Pb were noted in the fine sand fraction, they also noted that available Pb concentrations were also high in the clay fraction [53]. Al-Oud and others found that Cd mobility decreases with increasing amounts of iron oxide fractions; silt content and exchangeable Mg 2+ in the soils; and showed that Cd mobility is higher in those soils with a high percentage of sand [54]. Additionally, Bloomfield has found that microbial action has also been observed to mobilize Pb, Zn and Cu from the carbonate and oxide residuals within soils [55] and Ernst established that solubility of metals was also enhanced by the acidification of the soil by bacteria [56].…”
Section: Ellis Island Soil Particle Sizementioning
confidence: 95%
“…iron oxide fractions; silt content and exchangeable Mg 2+ in the soils; and showed that Cd mobility is higher in those soils with a high percentage of sand [54]. Additionally, Bloomfield has found that microbial action has also been observed to mobilize Pb, Zn and Cu from the carbonate and oxide residuals within soils [55] and Ernst established that solubility of metals was also enhanced by the acidification of the soil by bacteria [56].…”
Section: Ellis Island Soil Particle Sizementioning
confidence: 99%
See 1 more Smart Citation